The influence of open-ended and STAD method on the mathematical problem-solving skills in terms of learning achievement - Alman Alman (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2017)
This study is a quasi-experimental research using factorial design. This study aimed at finding the facts that had been resulted from the different influence caused by the use of Open-Ended method and that of STAD method on the students’ mathematical problem-solving skills in terms of learning achievement. The learning achievement was categorized into two types namely the high achievement and the low achievement. The population in this study was Grade V students from SD Negeri Serayu. The data were analyzed by ANAVA univariate test. The results of the study were as follows. First, there have been differences in the mathematical problem-solving skills of the students who had been taught using Open-Ended method and those who had been taught using the STAD method. Second, there were also differences on the students’ score. For the students who had been taught using the Open-Ended method, the highest posttest average score of their learning achievement was 95.71 while the lowest post-test average score of their learning achievement was 63.92. These students’ total average score of learning achievement was 81.04. On the other hand, for the students who had been taught using STAD the highest posttest average score of their learning achievement was 95.50 while the lowest posttest average score of their learning achievement was 70.00. These students’ total average score of learning achievement was 89.13. Third, there has not been any differences between the Open-Ended method and the STAD method.